Optimizing antibiotic prescribing for acute respiratory tract infections in German primary care: results of the regional intervention study CHANGE-3 and the nested cRCT - Feldmeier, Gregor; Löffler, Christin; Altiner, Attila; Wollny, Anja; Garbe, Katharina; Kronsteiner, Dorothea; Köppen, Martina; Szecsenyi, Joachim; Leyh, Mirko; Voss, Arwed; Kamradt, Martina; Poß-Doering, Regina; et al. (Antibiotics, 2023)
Within primary care, acute respiratory tract infections (ARTIs) are the most common reason for prescribing antibiotics. The aim of the CHANGE-3 study was to investigate how antibiotic prescribing for non-complicated ARTIs can be reduced to a reasonable level. The trial was conducted as a prospective study consisting of a regional public awareness intervention in two regions of Germany and a nested cluster randomised controlled trial (cRCT) of a complex implementation strategy. The study involved 114 primary care practices and comprised an intervention period of six winter months for the nested cRCT and two times six winter months for the regional intervention. The primary outcome was the percentage of antibiotic prescribing for ARTIs between baseline and the two following winter seasons. The regression analysis confirmed a general trend toward the restrained use of antibiotics in German primary care. This trend was found in both groups of the cRCT without significant differences between groups. At the same time, antibiotic prescribing was higher in routine care (with the public campaign only) than in both groups of the cRCT. With regard to secondary outcomes, in the nested cRCT, the prescribing of quinolones was reduced, and the proportion of guideline-recommended antibiotics increased.